INTERFERENSI PENGGUNAAN BAHASA INDONESIA PADA SISWA KELAS VII SEKOLAH MENENGAH PERTAMA NEGERI 1 UBUD TAHUN 2021 - Ni Putu Parmini (Wacana Saraswati Majalah Ilmiah Tentang Bahasa Sastra Dan Pembelajarannya, 2021)
The purpose of this study was to determine the factors that cause interference among VII grade students of SMP Negeri 1 Ubud in 2021. The expectation of using Bahasa Indonesia properly and correctly has often been carried out. The use of Bahasa Indonesia among junior high school students, especially VII grade students, found that there were many deviations both inside and outside the classroom. Those deviations were found by the authors when observing during the learning process in class and during breaks outside the classroom. In addition, the results of the interview also showed that interference occurs and the causes of interference. The causes of interference in VII grade students of SMP Negeri 1 Ubud in 2021 were prestigious motives, waning loyalty to Indonesian, bilinguality on students, loss of vocabulary, the need to clarify speech, tendency to use foreign languages ​​and carry over of habits in local languages. This should be overcome by familiarizing and monitoring student communication in Bahasa Indonesia, both in the Bahasa Indonesia language learning process and other fields of study. Key words: Interference, Use of Bahasa Indonesia, VII Grade Students